Implementasi KKN Internasional melalui Video Korporat Surprising Kalumpang sebagai Upaya Promosi Wisata Lokal di Hulu Selangor, Malaysia - Aryandani, Rian; Rajendra, Muhammad (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Kalumpang in Hulu Selangor, Malaysia, holds immense tourism potential that remains underpromotion, spanning natural scenery, multicultural heritage, and unique historical legacy. This gap caught the attention of UNNES students through the KKN Mendunia program, a cross-border learning initiative positioning students as agents of global change. Using the Ipteks Diffusion method, the team produced a video titled "Surprising Kalumpang: Kalumpang Kan Ada" as a catalyst for regional tourism development. The video is designed to transform Kalumpang from an unknown destination into a sought-after travel spot. The production process involved field observation, interviews with local figures, community collaboration, and digital distribution via YouTube and Instagram. The result is more than audiovisual content, serving as a strategic tool to strengthen Kalumpang's identity and drive the local economy through tourism.